Leptin receptor expression in obesity-associated acanthosis nigricans - Essam El-Den Mohammed; Refaat R Mohammed; Ahmed A.E Abd Elhakeem; Amira A Riad (Wolters Kluwer Medknow Publications, 2020)
Introduction Obesity-associated acanthosis nigricans (AN) is the most common type of AN. Objective To detect leptin receptor expression in the skin lesion affected by obesity-associated AN. Patients and methods A total of 20 patients with obesity-associated AN were included in this prospective study. Complete history taking, thorough general examination, and calculation of BMI were done for all patients. Leptin receptor expression was investigated in skin lesion and perilesional skin by immunohistochemistry. Results The mean age of the patients was 19.5±7.561 years and the mean duration of the disease was 8.6±6.44 years. A total of 14 patients were females and six patients were males. The mean BMI of the examined patients was 31.5±4.4. The expression of leptin receptors was significantly higher in skin lesions than perilesional skin of the patients. Conclusion Leptin receptor expression was significantly higher in skin lesions affected by obesity-associated AN.